Long-term exercise training and inflammatory biomarkers in healthy subjects: a meta-analysis of randomized controlled trials - Wang, Ya-Hai; Tan, Jingwang; Zhou, Huan-Huan; Cao, Meng; Zou, Yu (Frontiers in Psychology, 2023)
Objective This meta-analysis investigated the effect of long-term exercise training (ET) including aerobic, resistance, and multicomponent ET on the levels of inflammatory biomarkers in randomized controlled trials (RCTs) involving healthy subjects. Methods We searched seven databases for articles until May 1st, 2023. A random-effect meta-analysis, subgroup analysis, meta-regressions as well as trim and fill method were conducted using STATA 16.0. Result Thirty-eight studies were included in the meta-analysis, involving 2,557 healthy subjects (mean age varies from 21 to 86 years). Long-term ET induced significantly decreased in the levels of interleukin-6 (IL-6) (SMD -0.16, 95% CI -0.30 to −0.03, p = 0.017), C-reactive protein (CRP) (SMD -0.18, 95% CI -0.31 to −0.06, p = 0.005), as well as tumor necrosis factor alpha (TNFα) (SMD -0.43, 95% CI -0.62 to −0.24, p < 0.001). Subgroup analysis revealed that Long-term ET conducted for more than 12 weeks and exercise of moderate intensity had greater anti-inflammatory effects. Meta-regression analysis showed that the reduction in CRP level induced by long-term ET was weakened by increasing exercise intensity. Conclusion Long-term ET induced significant anti-inflammatory effects in healthy subjects. Long-term ET-induced anti-inflammatory effects were associated with exercise of moderate intensity and training conducted for more than 12 weeks. Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/# myprospero, PROSPERO, identifier CRD42022346693.